Business Plan : Dungun Music Centre / Azri Haqimi Abd Manap & Mohd Hafrizal Che Harun - Abd Manap, Azri Haqimi; Che Harun, Mohd Hafrizal (2009)
Our company name is Dungun Music Centre that perform the selling of musical instrument and the service of jamming and recording studio, musical class and repairing the musical instrument. Our company consists of general manager which is Azri Haqimi Bin Abdul Manap, Operation and Administrative Manager Mohd Hafrizal Bin Che Harun and Financial Manager Muhd Azlan Bin Rozali. We want to introduce our company that is call Dungun Music Centre. Our nature of business is providing a studio for music training, sell the music instrument, service and repair the musical instrument and teach the music lesson. At our music centre we provide the studio and the instrument for the musician to do their practice. We also sell many type of musical instrument including traditional music instrument and the spare part of the instrument. Not just that, we also provide the service of repairing the music equipment doing by the expert and the music lesson that we provide are conducted by the professional. Our business is located at Block E 21, Pusat Pemiagaan Sura Gate, 23000, Dungun, Terengganu. We choose to establish our business right there because the location was strategic and easy to find for all of people. It located at the main centre of Dungun and the building is surround by the market where all of people most to go to. Our industry profile are include in the music Industry . The Malaysian government recognises that rapid economic growth must be accompanied by social, cultural and psychological progress for a truly improved quality of life (Prime Minister's Department 1996). Where in the past, encouragement of the arts and more specifically of music has been sporadic at best, recent developments have shown that the government is indeed serious in its campaign to promote serious music among the general public. Concrete steps which have been taken include the introduction of music into the New Integrated Secondary School Curriculum (Pusat Perkembangan Kurikulum 1994) by the Ministry of Education in 1995, as well as the setting up the National Arts Academy, National Symphony Orchestra and National Choir by the Ministry of Culture, Arts and Tourism in 1993. The government has also in recent years approved the setting up of several new degree programs in music at the various local universities. Many corporate based orchestras as well as private colleges which offer a variety of music certificates, diplomas and twinning degrees have also recently sprouted up under the auspices of the present conducive environment.